(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the unique priorities and distinctive aspects of India’s foreign policy in the new era. India’s multi-vector foreign policy is aimed at developing global cooperation while maintaining a balanced approach in its relations with key geopolitical players. The article examines India’s strategic partnerships with the United States, Russia, China, the European Union, and regional countries, as well as changes in economic and trade relations, and its activities in cultural diplomacy and regional security. Based on statistical data from 2024, the article analyzes new trends in India’s foreign policy and its role on the international stage.